Calcutta Madrasah: A historical journey from British to Independent India - Rahman, Obaidur (International Journal of Psychosocial Rehabilitation, 2020)
The Calcutta Madrasah was established by Warren Hastings, the governor-general of British India, in 1780. It is regarded as the first educational institution established by the British government in India. Initially, Calcutta Madrasah, or Mohammedan College, was placed on the shoulder of Maulana Majduddin, a great Islamic scholar and disciple of Shah Waliullah Dehlavi. In 1850, Dr. A. Springer was appointed the first principal of Calcutta Madarsah, and in 1854, the Anglo-Persian department was created. Initially the course curriculum of Madrasah was designed on the model of ‘Dars-e Nizamia,’ a leading Arabic-medium school that existed in Lucknow. On a later date, the subjects like medicine, mathematics, philosophy, and logic were included as well as the undergraduate program, which was introduced in 1863. An Anglo-Persian Department was also framed in 1854, and Islamic courses like Kalim, Fakhrul Muhaddithin, and Mumtazul Muhaddithin have been introduced in Calcutta Madrasah. After 1947, a part of Calcutta Madrasah had been shifted to Dhaka, with which numerous valuable and rare books and manuscripts had been shifted, and a number were lost forever. Finally, the Aliah University Act was passed by the West Bengal Legislative Assembly in 2007 for the upgrading of Calcutta Madrasah to Aliah University. The Act came into force on 5th April, 2008. This historic institution has produced eminent scholars and writers in the Indian subcontinent through its long journey for more than two hundred and fifty years.